Mechanochemical Activation of the Reaction of Tetraacetylglycoluril with Some Cyclic Primary Amines. Synthesis of Acetamides; Russian Journal of Organic Chemistry; Vol. 54, iss. 4 - Bakibaev A. A. Abdigali Abdimanapovich (2018, 2018)
Title screen